Building Businesses, Creating Communities: Residential Segregation and the Growth of African American Business in Southern Cities, 1880–1915 - Ingham, John N. (Business History Review, 2003)
Patterns of residential segregation in late-nineteenth-century southern cities had great influence on the type of African American business that developed. They also affected the relative stability of business enterprise. In neighborhoods with a higher degree of segregation, African American entrepreneurs were able to develop vital businesses that survived the worsening climate of race relations around the turn of the century.
Keywords: Business History and race